2016
DOI: 10.1515/gps-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous H2O2 direct synthesis process: an analysis of the process conditions that make the difference

Abstract: A trickle bed reactor (TBR) was used to study different process parameters upon hydrogen peroxide direct synthesis. The catalysts used were commercial palladium on active carbon. The influence of pressure (1.75-25 barg), temperature (5-60°C), liquid flow rate (2-13.8 ml·min -1 ), gas flow rate (3.4-58.5 ml·min -1 ), catalyst amount (90-540 mg), Pd percentage on the support (5% wt., 10% wt. and 30% wt. Pd/C) as well as promoter concentrations (0.0005-0.001 m) were all varied as process parameters to better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…On the basis of the LH mechanism, several DFT studies have explored the effects of coadsorbates , various facets, alloying effects, , and surface oxidation . Despite the theoretical advances in HPDS with DFT methods based on the LH mechanism, the studies showed the main reaction (H 2 O 2 production) to be kinetically unfavorable relative to the side reaction (H 2 O production), which is in contrast to experimental results reporting that H 2 O 2 production is kinetically more favorable than H 2 O production . Moreover, recent experimental findings suggested that the solvent and H + ion concentration play an important role in the HPDS reaction. These experimental results are difficult to explain with the LH mechanism.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…On the basis of the LH mechanism, several DFT studies have explored the effects of coadsorbates , various facets, alloying effects, , and surface oxidation . Despite the theoretical advances in HPDS with DFT methods based on the LH mechanism, the studies showed the main reaction (H 2 O 2 production) to be kinetically unfavorable relative to the side reaction (H 2 O production), which is in contrast to experimental results reporting that H 2 O 2 production is kinetically more favorable than H 2 O production . Moreover, recent experimental findings suggested that the solvent and H + ion concentration play an important role in the HPDS reaction. These experimental results are difficult to explain with the LH mechanism.…”
mentioning
confidence: 90%
“…18 Despite the theoretical advances in HPDS with DFT methods based on the LH mechanism, the studies showed the main reaction (H 2 O 2 production) to be kinetically unfavorable relative to the side reaction (H 2 O production), which is in tion. 28 Moreover, recent experimental findings suggested that the solvent and H + ion concentration play an important role in the HPDS reaction. 29−31 These experimental results are difficult to explain with the LH mechanism.…”
mentioning
confidence: 99%
“…Yield has been recognized as an essential factor to the competitiveness and sustainable development of a factory (Chen and Wang 2014). Elevating yield is also a critical task for green manufacturing, because a high yield minimizes scrap and rework, conserving materials, energy, time, and labor (Rusinko 2007;Zhang et al 2016;Huerta et al 2016). For these reasons, all factories have sought to enhance yield.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Additionally, the immiscibility of H 2 O 2 with nonpolar olefins in organic medium presents another major drawback. 13,14 Fluorinated alcohols are a class of extraordinary organic solvents with powerful dissolving ability while maintaining water-soluble properties. 15−19 Perfluorinated alcohols, particularly 1,1,1,3,3,3-hexafluoroisopropyl alcohol (HFIP) and 2,2,2-trifluoroethanol (TFE), were applied as solvents to catalytically activate H 2 O 2 in the absence of any metal oxides, permitting selective epoxidation of alkenes and Baeyer−Villiger oxidation of ketones.…”
mentioning
confidence: 99%
“…Catalytic oxidation of olefins to produce epoxides commonly takes place in the presence of oxidants such as peroxomonosulfate, percarbonic acids, or hypochlorites, which inevitably produces large amounts of chemical waste byproducts and is thus not economically promising. Hydrogen peroxide (H 2 O 2 ), as an affordable and environmentally benign oxidant, provides an attractive option for alkene epoxidation, which, however, requires additional catalysts mostly associated with transition-metal oxides to be electrophilically activated. , Additionally, the immiscibility of H 2 O 2 with nonpolar olefins in organic medium presents another major drawback. , …”
mentioning
confidence: 99%